2016
DOI: 10.1093/heapro/daw088
|View full text |Cite
|
Sign up to set email alerts
|

A research and evaluation capacity building model in Western Australia

Abstract: Evaluation of public health programs, services and policies is increasingly required to demonstrate effectiveness. Funding constraints necessitate that existing programs, services and policies be evaluated and their findings disseminated. Evidence-informed practice and policy is also desirable to maximise investments in public health. Partnerships between public health researchers, service providers and policymakers can help address evaluation knowledge and skills gaps. The Western Australian Sexual Health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…A lack of access to evaluation expertise and insufficient resources have been frequently identified as barriers to health promotion evaluation . Working in partnership with external evaluators has been proposed by practitioners as a potential solution to overcoming barriers to evaluation . Qualitative studies have also identified research‐practice partnerships as a facilitator to evaluation, particularly if there is an ongoing collaborative relationship with the program team .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of access to evaluation expertise and insufficient resources have been frequently identified as barriers to health promotion evaluation . Working in partnership with external evaluators has been proposed by practitioners as a potential solution to overcoming barriers to evaluation . Qualitative studies have also identified research‐practice partnerships as a facilitator to evaluation, particularly if there is an ongoing collaborative relationship with the program team .…”
Section: Discussionmentioning
confidence: 99%
“…While a number of generic health promotion evaluation frameworks exist, guidance and consistency of evaluation practices within an area of practice may facilitate higher quality evaluation . Such guidance is currently available to sexual health and blood borne virus health promotion and physical activity . Thirdly, this study builds on a wider body of research concerning evidence generation and use in health promotion and recommendations for capacity building to support the application of research into practice remain relevant, particularly in relation to leadership, organisational culture, policies, systems and structures, resource allocation and practitioner skills .…”
Section: Discussionmentioning
confidence: 99%
“…As medical knowledge advances there is increased collaboration among departments and institutions in both medical practice and research. 1719 It is likely that multidisciplinary and multi-institutional efforts would garner a higher number of authors even if not in the setting of randomized trials. For instance, multi-institutional consortia reporting large datasets for clinical outcomes or comparative effectiveness requires authors to be represented from a number of different departments or institutions.…”
Section: Discussionmentioning
confidence: 99%
“…SiREN facilitates and participates in partnerships between research, government and non-government organisations to apply for competitive grant funding and undertake research and evaluation projects; provides tailored project planning, research and evaluation support; provides web-based resources to support evidence-informed policy and practice; hosts a biennial research and evaluation symposium that brings together those working in sexual health or bloodborne viruses across Australia; and maintains a network (database) of approximately 300 professionals with whom it shares relevant research and evaluation evidence, news, funding opportunities and events via electronic mail. A detailed description of the SiREN model has been published elsewhere 9…”
Section: Introductionmentioning
confidence: 99%
“…Despite their potential, there is scant evidence describing the kinds of long-term changes that can be achieved by these partnerships, and of the processes that lead to these changes 15. Evaluations of SiREN conducted 2 and 3 years after its inception established that SiREN had contributed to improving research, evaluation and evidence-informed practice, attitudes, skills and knowledge 9 16. While these short-term impacts are promising, exploration of long-term outcomes and the processes by which these are achieved is important given the potential of partnership models, like SiREN, to support the practice of public health.…”
Section: Introductionmentioning
confidence: 99%